2008
DOI: 10.1111/j.1365-2915.2008.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a fuller understanding of mosquito behaviour: use of electrocuting grids to compare the odour‐orientated responses ofAnopheles arabiensisandAn. quadriannulatusin the field

Abstract: . The epidemiological role of and control options for any mosquito species depend on its degree of ' anthropophily ' . However, the behavioural basis of this term is poorly understood. Accordingly, studies in Zimbabwe quantified the effects of natural odours from cattle and humans, and synthetic components of these odours, on the attraction, entry and landing responses of Anopheles arabiensis Giles (Diptera: Culicidae) and Anopheles quadriannulatus Theobald. The numbers of mosquitoes attracted to human or catt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 32 publications
9
90
1
Order By: Relevance
“…However, the complexity of these models, and their reliance upon local measurements of several entomological input parameters, all of which have limited precision and accuracy, may well limit broader application of this approach beyond the crude application to existing data presented in Figure  2. Recent attempts to rejuvenate and improve existing entomological survey methodology for detecting resource utilization attempt events with electrified grids [8486], sticky traps [77, 87], mechanized aspirators [70], and high resolution cameras [75, 76], should enable improved sensitivity of utilization attempt event detection at surveyed samples of resource subset targets. However, while such technical advances may well address the inaccuracies of attempts to estimate utilization rates for subsets of resting sites or other non-nutritional resources by improving event detection sensitivity, they are unlikely to improve their precision because considerable uncertainty arises from the need for relatively complex models (Equations 25a, 25b and 30) that require correspondingly numerous measurements of input parameters.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complexity of these models, and their reliance upon local measurements of several entomological input parameters, all of which have limited precision and accuracy, may well limit broader application of this approach beyond the crude application to existing data presented in Figure  2. Recent attempts to rejuvenate and improve existing entomological survey methodology for detecting resource utilization attempt events with electrified grids [8486], sticky traps [77, 87], mechanized aspirators [70], and high resolution cameras [75, 76], should enable improved sensitivity of utilization attempt event detection at surveyed samples of resource subset targets. However, while such technical advances may well address the inaccuracies of attempts to estimate utilization rates for subsets of resting sites or other non-nutritional resources by improving event detection sensitivity, they are unlikely to improve their precision because considerable uncertainty arises from the need for relatively complex models (Equations 25a, 25b and 30) that require correspondingly numerous measurements of input parameters.…”
Section: Discussionmentioning
confidence: 99%
“…E-targets baited with human odour may serve as models of humans that would allow us to measure the numbers of vectors that are attracted to humans with or without a repellent without exposing the subjects to risk. Electric nets have been shown to be effective against a wide range of vectors, including mosquitoes (Torr et al, 2008), and thus the methods described in this study could be readily applied to studies of mosquito-borne diseases of humans.…”
Section: Quantifying Protectionmentioning
confidence: 99%
“…These can range from the ubiquitous bednets and window screens designed specifically to protect against biting insects through to the 'inadvertent' protection provided by being within a house, which many species of mosquito are inhibited from entering (Lindsay et al, 2003;Torr et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have also shown higher attraction of An. arabiensis to human than cow odour Torr et al, 2008;, while other studies show that An.…”
Section: Discussionmentioning
confidence: 73%
“…gambiae in both field and laboratory studies Pates et al, 2001;Takken & Verhulst, 2013), only a few studies have reported An. arabiensis to be more attracted to human compared to cow odour Torr et al, 2008;Takken & Verhulst, 2013 …”
Section: Discussionmentioning
confidence: 99%